ADVERSITY QUOTIENT TERHADAP SELF CONTROL DAN SELF SUCCES MAHASANTRI TAKHOSUS ILMU FAROID DI MA’HAD ALY NURUL JADID - Hambali Hambali; Kartika Rahmania (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2021)
Every individual who takes part in the learning process can certainly have high learning achievement. To achieve this achievement is not easy, there will be many difficulties and challenges that must be faced, even if it is possible to experience a failure. Not all individuals can go through difficulties and challenges in the learning process which results in difficulty achieving the desired success. Of the many abilities needed to face life's difficulties, including difficulties in achieving achievement, namely the adversity quotient ability needed to achieve success in life. Self-control can also help a person to achieve success. Someone who has a high adversity quotient and can control themselves can achieve success despite many obstacles, they do not immediately give up and do not let difficulties destroy their dreams and ideals. Individuals who have high adversity quotient abilities will continue to achieve the highest possible achievement, because achievement is a success that is wanted to be achieved and the goals of every student. In this paper, the author describes by researching 20 mahasantri takhosus science of faroid in Ma'had Aly Nurul Jadid to find out the level of adversity quotient they have and their relationship with self-control and the success they will get.